2009
DOI: 10.1136/bmj.b3360
|View full text |Cite
|
Sign up to set email alerts
|

Radial extracorporeal shockwave treatment compared with supervised exercises in patients with subacromial pain syndrome: single blind randomised study

Abstract: Objective To compare the effectiveness of radial extracorporeal shockwave treatment with that of supervised exercises in patients with shoulder pain. Design Single blind randomised study. Setting Outpatient clinic of physical medicine and rehabilitation department in Oslo, Norway. Participants 104 patients with subacromial shoulder pain lasting at least three months. Interventions Radial extracorporeal shockwave treatment: one session weekly for four to six weeks. Supervised exercises: two 45 minute sessions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
4
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 37 publications
7
100
4
4
Order By: Relevance
“…The findings of this current study are in keeping with other similar studies where superiority of one approach over an active comparator is not apparent [20,21]. In contrast to other studies, the patient reported outcomes in terms of change in SPADI score at three months post-randomisation in this current study might be regarded as relatively meagre; 12.4 points for the self-managed exercise group and 16.7 points for the usual physiotherapy group.…”
Section: Discussioncontrasting
confidence: 55%
“…The findings of this current study are in keeping with other similar studies where superiority of one approach over an active comparator is not apparent [20,21]. In contrast to other studies, the patient reported outcomes in terms of change in SPADI score at three months post-randomisation in this current study might be regarded as relatively meagre; 12.4 points for the self-managed exercise group and 16.7 points for the usual physiotherapy group.…”
Section: Discussioncontrasting
confidence: 55%
“…37 Nevertheless, surgery and exercises compared with a placebo laser have been reported to have statistical differences, 38 and an intervention with exercises produced higher improvement than shockwave therapy after 6 weeks. 39 The results in our study are similar to those reported in the treatment with proprioceptive exercises and conventional physiotherapy. 40 …”
Section: Discussionsupporting
confidence: 82%
“…[29][30][31][32][33][34][35][36][37][38][39][40] Three RCTs investigated participants with persistent subacromial impingement syndrome, 29,31,32,35,36 and 2 addressed subacromial impingement syndrome of variable duration. 38,39 Two RCTs studied persistent nonspecific shoulder pain, 30,33 2 targeted participants with variable duration nonspecific shoulder pain, 34,37 and 1 addressed rotator cuff tendinitis of variable duration.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of those, 15 studies (published in 19 articles) were eligible for critical appraisal. [29][30][31][32][33][34][35][36][37][38][39][40][52][53][54][55][56][57][58] Ten studies (published in 12 articles) had low risk of bias and were included in the best evidence synthesis. [29][30][31][32][33][34][35][36][37][38][39][40] The interrater agreement for the screening of titles and abstracts was κ = 0.91 (95% CI, 0.82-1.00).…”
Section: Study Selectionmentioning
confidence: 99%